Stage-dependent biomarker changes in spinocerebellar ataxia type 3 - Faber, Jennifer; Berger, Moritz; Wilke, Carlo; Hubener-Schmid, Jeannette; Schaprian, Tamara; Santana, Magda M.; Grobe-Einsler, Marcus; Onder, Demet; Koyak, Berkan; Giunti, Paola; Garcia-Moreno, Hector; Gonzalez-Robles, Cristina; et al. (Annals of neurology, 2024)
Spinocerebellar ataxia type 3/Machado-Joseph disease is the most common autosomal dominant ataxia. In view of the development of targeted therapies, knowledge of early biomarker changes is needed. We analyzed cross-sectional data of 292 spinocerebellar ataxia type 3/Machado-Joseph disease mutation carriers. Blood concentrations of mutant ATXN3 were high before and after ataxia onset, whereas neurofilament light deviated from normal 13.3 years before onset. Pons and cerebellar white matter volumes decreased and deviated from normal 2.2 years and 0.6 years before ataxia onset. We propose a staging model of spinocerebellar ataxia type 3/Machado-Joseph disease that includes a biomarker stage characterized by objective indicators of neurodegeneration before ataxia onset. ANN NEUROL 2023
Online veröffentlicht: 14 November 2023
Gesehen am 05.02.2024